AN OVERVIEW OF MOTHER KNOWLEDGE AFTER GIVING BIRTH ABOUT EXCLUSIVE BREASTFEEDING - Ninna Rohmawati (UNEJ e-Proceeding)
Infant mortality rate is one indicators used toascertaining of community health degree. Infantmortality closely related with family education level,social economy of family, value system, customs,cleanliness, health environmental, health servicesavailable, childbirth problem, provision ofimmunization and malnutrition. Incident ofmalnutrition in infants caused by bestowalbreastfeeding is wrong and provision ofsupplementary food improper. So provisionbreastfeeding patterns and provision ofsupplementary food proper must be attention1.Breastfeeding is best food for babies in early ages hislife, good physiologically and biological.Breastfeeding containing nutrients, substanceimunogenik to protect a baby from infection2.Breastfeeding rich in carotenoids and selenium, sothat breastfeeding had a role in defense system thebody of a baby to prevent various diseases. Everydrop breastfeeding also contain minerals andenzymes to prevention of disease and antibodiesmore effective than and formula milk3. Manyresearch show the benefit of exclusivebreastfeeding4. World Health Organization (WHO)recommend to give exclusive breastfeeding for thefirst six months to achieve the growth optimal,development and health.After that, babies have toprovided with food a companion nutritious andremain suckling until two years5. Exclusivebreastfeeding is breastfeeding given to a baby eversince born during six months, without adding and orreplace with food or drink other6.Based on world health organization in 2010, 1.5million children below five 0-6 months died of theprovision of supplementary food before the time,and in the provision of breastfeeding around theworld to 15 % of infants given breastfeeding, theprovision of breastfeeding lowest in central Africaand North Africa, Asia and America Latin. Based onHealth research for basic (Riskesdas) 2013 show forgranting breastfeeding in Indonesia has been good ifcompared with the results of Riskesdas 2010 thatonly covers 15.3 %7. Based on health departmentdata at 2010 in east java obtained the scope ofprovision of exclusive breastfeeding for 6 months atprovincy as many as 31,21 %8. Exclusivebreastfeeding program for six months, hasundertaken in Jember regency since the issuance ofIndonesian Kepmenkes no.450/Menkes/IV/2004 inan effort to improve a baby or child toddlersnutritions. But, Jember regency still not reach thegoal of program that has been set is as much as 80%9. In 2010, the scope of provision of exclusivebreastfeeding in Jember regency as much as 67,10%8. Therefore, needed a special act to increase it, sothe targets can be achieved. Many factor thatinfluences mother in decide on and do provisionpatterns breastfeeding, especially physical andpsychological mother not ready, lack of informationand knowledge on benefits breastfeeding,management of lactation10. Mothers that giveexclusive breastfeeding said the real questionrelated knowledge of breastfeeding as many as40,7% and mother who do not give exclusivebreastfeeding said the real question relatedknowledge of breastfeeding as many as 29.6 %. Thisshows there was a significant correlation betweenlevel of knowledge mother about breastfeeding withprovision of exclusive breastfeeding11.